2012
DOI: 10.1007/s00520-012-1474-z
|View full text |Cite
|
Sign up to set email alerts
|

Advanced prostate cancer as a cause of oncogenic osteomalacia: an underdiagnosed condition

Abstract: This case suggests that TIO has a dismal prognosis in prostate cancer patients. The clinical oncology community must be aware about such disturbance that can be present in those patients with weakness, bone pain, and hypophosphatemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…Except for the elaboration of phosphatonins, the tumours associated with pTIO are remarkably innocuous and harmless per se, although rare associations with malignant neoplasms such as prostatic carcinoma, osteosarcoma and renal cell carcinoma have been reported. 1,8,9 Thus, patients have a unique opportunity of complete cure from their debilitating osteomalacia if these tumours can be localized and excised. However, localizing these often small sized, clinically inapparent tumours that can be present anywhere in the body from head to toes is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the elaboration of phosphatonins, the tumours associated with pTIO are remarkably innocuous and harmless per se, although rare associations with malignant neoplasms such as prostatic carcinoma, osteosarcoma and renal cell carcinoma have been reported. 1,8,9 Thus, patients have a unique opportunity of complete cure from their debilitating osteomalacia if these tumours can be localized and excised. However, localizing these often small sized, clinically inapparent tumours that can be present anywhere in the body from head to toes is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal tumors are seen in elderly and associated with FGF23 over-production and urine P i wasting, hypophosphatemia, 1,25(OH) 2 D deficiency and osteomalacia [110,111]. Rare forms of FGF23 gain-of-function [112] and loss-of-function [113] mutations can cause familial forms of hyper- or hypophosphatemia, vitamin D alterations and soft-tissue injury.…”
Section: Fibroblast Growth Factor-23mentioning
confidence: 99%
“…It is most often seen with mesenchymal tumors, though a literature review spanning thirty-four years revealed 24 case reports of this syndrome in patients with metastatic prostate cancer [17]. Two more cases have been reported since [18,19]. Unfortunately, we do not have a baseline serum phosphorous level for the first patient, and he declined follow-up after discontinuing abiraterone.…”
Section: Case 2 Journal Of Case Reports and Studiesmentioning
confidence: 92%